2011
DOI: 10.1075/eurosla.11.10jud
|View full text |Cite
|
Sign up to set email alerts
|

L1/L2 parametric directionality matters

Abstract: Assuming transfer of the L1 grammar, in the present study the question of whether all parameters can be reset even with access to UG is examined in light of the subset/superset relationship. Specifically, the resetting of the Null Subject Parameter (NSP) in L2 learners of English (L1 Spanish) is investigated by means of examining the application of the Overt Pronoun Constraint (Montalbetti 1984), a property that clusters with the null subject setting only, as well as acceptance/rejection of null subjects in En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, Kanno (1997) nds that L1 English learners of Japanese have close-to-native command of null subjects across a number of syntactic and discourse contexts. By contrast, even near-native L2 learners of English fail to consistently use the expletive subject (Judy 2011), the true hallmark of the obligatory subject grammar. The variational learning model provides a straightforward account for these cross-linguistic ndings.…”
Section: Ug Access and Input Frequencymentioning
confidence: 93%
“…For example, Kanno (1997) nds that L1 English learners of Japanese have close-to-native command of null subjects across a number of syntactic and discourse contexts. By contrast, even near-native L2 learners of English fail to consistently use the expletive subject (Judy 2011), the true hallmark of the obligatory subject grammar. The variational learning model provides a straightforward account for these cross-linguistic ndings.…”
Section: Ug Access and Input Frequencymentioning
confidence: 93%
“…In other words, having transferred a superset from the L2 may prevent the L3 learner from being able to reduce that superset into the subset relevant to the L3 grammar. Judy and Rothman (2010) and Judy (2011) showed that the predictions of the subset principle and FT/FA were supported. Despite high proficiency in L2 English, the Spanish natives did not show consistent evidence of NSP resetting for L2 English, ultimately continuing to accept null expletives in English, especially in embedded contexts, and misapplying the OPC in anaphora resolution.…”
Section: Why L3/ln Acquisition Must Not Be Regarded As Another Instanmentioning
confidence: 99%
“…Following from the predictions of the full transfer/full access (FT/FA) model of the initial state (Schwartz & Sprouse, 1996), Judy and Rothman (2010) and Judy (2011) tested Spanish native speakers of highly advanced L2 English proficiency with the same NSP properties. Their prediction was that Spanish natives would not be able to reset the NSP, despite what has been robustly shown in the opposite direction (for review of the many studies that show this, see Rothman, 2009), not because UG is inaccessible, but rather because the Spanish setting of the NSP constitutes a proper superset to the English subset value.…”
Section: Why L3/ln Acquisition Must Not Be Regarded As Another Instanmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to do so, they must rely on indirect negative evidence, which consists in the nonappearance of an ungrammatical structure in the L2 input (Carroll, 2001, pp. 18–19, 116; Gabriele, 2009; Gass & Mackey, 2002; Judy, 2011), and that is thus different from direct negative evidence, that is, overt corrections by teachers or interlocutors. Unlearning an L1 rule merely on the basis of indirect negative evidence is a difficult task, and one that learners often fail to accomplish even after long exposure to the L2 (Bowles & Montrul, 2008; Judy, 2011; Lefebvre, White, & Jordan, 2006).…”
mentioning
confidence: 99%